2000
DOI: 10.1038/35050128
|View full text |Cite
|
Sign up to set email alerts
|

Co-assembly of polycystin-1 and -2 produces unique cation-permeable currents

Abstract: The human kidney is composed of roughly 1.2-million renal tubules that must maintain their tubular structure to function properly. In autosomal dominant polycystic kidney disease (ADPKD) cysts develop from renal tubules and enlarge independently, in a process that ultimately causes renal failure in 50% of affected individuals. Mutations in either PKD1 or PKD2 are associated with ADPKD but the function of these genes is unknown. PKD1 is thought to encode a membrane protein, polycystin-1, involved in cell-cell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
787
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 757 publications
(823 citation statements)
references
References 25 publications
32
787
3
1
Order By: Relevance
“…Some of the biophysical properties such as cation selectivity and regulation by Ca 2+ were in agreement with a previous study on the structurally related channel, PKD2L1 [30]. In the PKD1-PKD2 coexpression study [29], it was also shown that PKD1 facilitated the targeting of PKD2 to the plasma membrane which was necessary for channel activity. In further support of the relevance of the interaction to ADPKD, naturally occurring mutations in PKD1 or PKD2 that would eliminate their interaction resulted in loss of channel activity.…”
Section: Functional Compartmentalization Of Pkd2supporting
confidence: 90%
See 3 more Smart Citations
“…Some of the biophysical properties such as cation selectivity and regulation by Ca 2+ were in agreement with a previous study on the structurally related channel, PKD2L1 [30]. In the PKD1-PKD2 coexpression study [29], it was also shown that PKD1 facilitated the targeting of PKD2 to the plasma membrane which was necessary for channel activity. In further support of the relevance of the interaction to ADPKD, naturally occurring mutations in PKD1 or PKD2 that would eliminate their interaction resulted in loss of channel activity.…”
Section: Functional Compartmentalization Of Pkd2supporting
confidence: 90%
“…Function at the plasma membrane-Functional expression of PKD2 as an ion channel was first reported by Hanaoka et al [29]. In this study, it was demonstrated that PKD2 alone was unable to form a functional channel in CHO-K1 cells, but in association with PKD1, PKD2 displayed channel activity.…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 78%
See 2 more Smart Citations
“…A likely candidate is the TRPP1/TRPP2 (or polycystin-1/polycystin-2) complex [61]. The precise functions of TRPP1 and TRPP2 (transient receptor potential polycystin 1 and 2) are not completely understood, but there is growing evidence that TRPP2 might function as a Ca 2+ -regulated/Ca 2+ permeable cationic channel and that TRPP1 is a regulator or sensor of this channel [62]. TRPP1 has previously been shown to be expressed in the presumptive pronephric territory in intact Xenopus embryos and in animal caps treated with activin A and RA [63].…”
Section: Trp Channels Are Involved In the Generation Of The Ca 2+ Sigmentioning
confidence: 99%